2009
DOI: 10.1086/596736
|View full text |Cite
|
Sign up to set email alerts
|

Low-Abundance Drug-Resistant Viral Variants in Chronically HIV-Infected, Antiretroviral Treatment–Naive Patients Significantly Impact Treatment Outcomes

Abstract: Ultra-deep sequencing identified a significantly larger proportion of HIV-infected, treatment-naive persons as harboring drug-resistant viral variants. Among participants who initiated treatment with the NNRTI strategy, the risk of VF was significantly greater for participants who had low- and high-prevalence NNRTI-resistant variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
448
2
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(470 citation statements)
references
References 19 publications
19
448
2
1
Order By: Relevance
“…These results were also limited by the inability of bulk sequencing technology to detect low-frequency variants that had been shown to affect treatment outcomes, [48][49][50][51][52][53] and that patients with HPLC-MS/ MS detectable pretherapy plasma drug levels were included in all virologic outcome analyses because HPLC-MS/MS was not performed on plasma samples with wildtype viruses. Our results agreed with reports that subtype-D infection was not associated with a worse virologic outcome, 54,55 which implied that the observed difference in suppression was not biased by subtype differences.…”
Section: Discussionmentioning
confidence: 99%
“…These results were also limited by the inability of bulk sequencing technology to detect low-frequency variants that had been shown to affect treatment outcomes, [48][49][50][51][52][53] and that patients with HPLC-MS/ MS detectable pretherapy plasma drug levels were included in all virologic outcome analyses because HPLC-MS/MS was not performed on plasma samples with wildtype viruses. Our results agreed with reports that subtype-D infection was not associated with a worse virologic outcome, 54,55 which implied that the observed difference in suppression was not biased by subtype differences.…”
Section: Discussionmentioning
confidence: 99%
“…9,24 In addition, we recently reported that such a technique is applicable to all PCR products. Grossmann et al 25 published a study where this assay was applied to sequence CEBPA, a gene with high GC content.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of adequate monitoring, the increased access to ART might lead to spread of transmitted and acquired drug-resistant HIV-1, resulting in reduced effectiveness of these drugs. Drug-resistant viruses have been reported to become the major circulating virus populations in infected individuals, with subsequent failure of therapy in treatment-naive patients [12,44,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of ART resistance is described as a predictor of immunologic, virologic, and clinical outcomes of therapy [10]. Consequently, the identification of HIVDR in treatment-naive patients is critical to maximize the detection of transmitted drug resistance, guide the selection of treatment regimen to suppress HIV-1 replication, and ultimately prevent resistance-associated virologic failure [9,11,12]. The prevalence of HIVDR among ART-naive people in the United States and Europe has been estimated to be 10%-15% [11,13].…”
Section: Introductionmentioning
confidence: 99%